Increased risk of disseminated cryptococcal infection in a patient with multiple sclerosis on fingolimod. (2020) - Kaur, Pushpinder; Lewis, Alana; Basit, Abdul; Cyr, Nikolas St; Muhammad, Zaman
Abstract: Multiple sclerosis (MS) is the most common autoimmune disease of the central nervous system (CNS), with an estimated 2.3 million people being affected globally, and is a major cause of permanent disability. About 90 % of the affected patients with MS have relapsing-remitting type. Fingolimod became the first FDA approved oral drug in 2010 with an immunomodulating mechanism to control the relapse rates. However, since its introduction, increased cases of cryptococcal infections have been reported including meningoencephalitis and disseminated infections. Herein, we present the case of a 34-year-old-male with disseminated Cryptococcal and localized varicella zoster virus (VZV) coinfection to highlight the risk of opportunistic infections associated with the long-term use of fingolimod. The objective of this literature review is for clinicians to have a high index of suspicion for cryptococcal infections when dealing with MS patients on Fingolimod, especially those who present with neurological symptoms, as this mimics MS relapse.